A model for artistic research - Correia, Jorge Salgado (2020)
The series of Cahiers of artistic research, created at IMPAR, University of Aveiro/INET-md, respond to the responsibility and the need to offer - first and foremost to our students, but also to the broader academic community - consistent guidance to assist the conception, design and development of artistic research projects. The aim of this series of Cahiers is to establish an alternative path for artistic research. Firmly grounded in the articulation between declarative and procedural knowledge, the 1st Cahier took the first steps along this path and constitutes an attempt to clearly define when research is artistic research. The second Cahier was published in January 2019 to complement the epistemological foundations proposed in the first Cahier launching two premises whose distinctive feature is to dictate the inextricable complementarity and complicity between artistic production and its respective clarification. Resuming, it was proposed that clarification should be understood as a written contribution - possibly reinforced by other media - which would have the dual function of improving our aesthetic experience and elucidating on the consequent mythopoetic reconfiguration. The mythopoetic reconfiguration would result from a process of reflection that should specify the relevance of the artistic intervention - within the social/artistic fields in which it intervenes - and would be based on four steps: scepticism, criticism of old mythopoetic constructions, ethical decisions and, finally, systematisation. It was suggested that clarification should be recognized as a contribution to knowledge according to its potential to promote empathetic communication. Emerging from the articulation of narrative and paradigmatic modes of knowledge, material thinking was suggested to be clarification's mode of knowledge. Material thinking is grounded on embodied meaning, is communicated in co-presence only, and therefore appeals to empathy. It follows that artistic research does not necessarily depend on the traditional academic research methods of observation and analysis, which belong to the paradigmatic mode of knowledge. Structure of this volume Built in a two-dimensional text that juxtaposes narrative and paradigmatic modes of discourse, this 3rd Cahier proposes artistic research as a trans-disciplinary field dedicated to artists interested in triangulating different modes of knowledge to realize the full potential of their artistic practices. This volume is structured in four parts. First, we present a short overview of the main points discussed in the 2nd Cahier, adding some new inputs concerning the processes of knowledge production and communication. Secondly, we look more closely at the notion of mythopoetic configurations: the role they play within humanity and their relationship with artistic research. Thirdly, we discuss the role of gestures in the process of reconfiguring new mythopoetic narratives, elaborating on the notion of Exemplarization proposed by Lehrer (2012). Finally, in the fourth part, we present an explanatory model for artistic research based on the intersection of three fundamental spheres: Ethics, Remix Culture and Aesthetic Appreciation.